A Tale of Two “Sisikus”: The Evolving Trajectory of the Anglophone Crisis in Cameroon - Fon, Nguh Nwei Asanga; Formella, Collins Nkapnwo; Achu, Nancy Ngum (Afrika Tanulmányok / Hungarian Journal of African Studies, 2023)
Cameroon has been plunged into a devastating civil conflict since December 2017 when President Paul Biya declared war on secessionists after the killing of four soldiers and two police officers in the South West Region. This paper approaches the Cameroon Anglophone Crisis from the theoretical premise of remedial secession. It argues that the evolution of the crisis from a moderate return to federalism pursued by “Sisiku” Agbor Felix Nkongho to the radical secession espoused by “Sisiku” Julius Ayuk Tabe can be understood within the framework of remedial secession. The cogency of this argument is examined against efforts made by the Cameroon government to tackle the crisis and the concept of territorial integrity. This paper concludes that the protracted nature of the conflict reflects the theoretical impasse between remedial secession and territorial integrity.